Lipschitz Estimates for Commutators of $p$-adic Fractional Hardy Operators (Communications in Mathematical Research, 2021)
In this paper, the boundedness of commutators generated by the $n$-dimensional fractional Hardy operators and Lipschitz functions on $p$-adic functionspaces are obtained. The authors show that these commutators are bounded on Herzspace and Lebesgue space with suitable indexes. Moreover, the commutator of Hardy-Littlewood-Polyá operator is also considered.